Novel Isochroman Dimers from Stachybotrys sp. PH30583: Fermentation, Isolation, Structural Elucidation and Biological Activities - Li, Wei; Yang, Ya-Bin; Yang, Xue-Qiong; Xie, Hui-Ding; Shao, Zhi-Hui; Zhou, Hao; Miao, Cui-Ping; Zhao, Li-Xing; Ding, Zhong-Tao (Planta Medica, 2017)
The rare anishidiol and five new isochromans, including three novel dimers with unprecedented skeletons, were isolated from Stachybotrys sp. PH30583. Their structures were determined by spectral analyses. The bioactivities of these compounds were also investigated. The dimers (6–10) inhibited acetylcholinesterase at 50 µM, but the monomers did not. To investigate the biogenesis of the novel dimers, a time-course investigation of metabolite production was undertaken.
Keywords: Stachybotrys sp.; Hypocreales; isochroman; bioactivity; dimer; anti-acetylcholinesterase